From Example Problems
Revision as of 21:55, 21 October 2006 by Geoff (Talk | contribs)

(diff) ← Older revision | Latest revision (diff) | Newer revision → (diff)
Jump to: navigation, search


f'(x)=\lim _{{\Delta x\to 0}}{\frac  {h(x+\Delta x)-h(x)}{\Delta x}}=\lim _{{\Delta x\to 0}}{\frac  {f(x+\Delta x)+g(x+\Delta x)-(f(x)+g(x))}{\Delta x}}

=\lim _{{\Delta x\to 0}}{\frac  {f(x+\Delta x)-f(x)}{\Delta x}}+\lim _{{\Delta x\to 0}}{\frac  {g(x+\Delta x)-g(x)}{\Delta x}}=f'(x)+g'(x)

Thus, the derivative of a sum is the sum of the derivatives.


Main Page : Calculus